An efficient one-pot access to N-(pyridin-2-ylmethyl) substituent biphenyl-4-sulfonamides through water-promoted, palladium-catalyzed, microwave-assisted reactions1. Issue 92 (8th October 2015) - Huang, Zhi-You; Yang, Jing-Fang; Chen, Qian; Cao, Run-Jie; Huang, Wei; Hao, Ge-Fei; Yang, Guang-Fu
<x xml:space="preserve">Abstract</x> An efficient one-pot, Pd(PPh3)4 catalyzed, water-promoted method with excellent substrate scope and functional group compatibility for the synthesis of N-(pyridin-2-ylmethyl) biphenyl-4-sulfonamides was developed under microwave irradiation.